Elucidation of the antipyretic and anti-inflammatory effect of 8-O-Acetyl Shanzhiside methyl ester based on intestinal flora and metabolomics analysis - Li, Xiaolin; Liu, Tianlong; Liang, Keke; Wang, Renjie; Yang, Jun; Chen, Yidan; Wang, Rong; Li, Maoxing (Frontiers in Pharmacology, 2025)
IntroductionPhlomoides rotata (Benth. ex Hook.f.) Mathiesen (syn. Lamiophlomis rotata (Benth. ex Hook.f.) Kudô) (P. rotate) is a traditional Tibetan medicine known for its hemostatic, analgesic, and anti-inflammatory effects, as well as its high content of 8-O-Acetyl Shanzhiside methyl ester (8-OaS). Clinical and experimental studies have reported gastrointestinal side effects, such as diarrhea, loose stools, even to black stools, associated with P. rotata. Given the bitter taste characteristic, laxative and antipyretic effects of iridoid glycosides, this study aims to investigate the antipyretic and anti-inflammatory effects of 8-OaS (the primary iridoid glycosides of P. rotate) on yeast-induced pyrexia in rats. Additionally, the role 8-OaS in modulating the intestinal flora composition and metabolome profile is explored.MethodsThe pyretic rat model was established by injected subcutaneously with 20% dry yeast suspension. Serum, hypothalamic tissues and colon content were collected for the assessment of relevant indicators. The peripheral inflammatory factors and central thermoregulatory mediators were assessed using enzyme-linked immunosorbent assay (ELISA). The expressions of mRNA and protein in hypothalamic tissue were evaluated through polymerase chain reaction (PCR), immunohistochemistry, and western blotting. 16S rDNA sequencing and LC-MS/MS were performed to determine the alteration and correlation of the intestinal flora and neurotransmitters in the colonic contents and hypothalamus.Results and discussion:Results show that 8-OaS treatment reduced pyrogenic cytokines (such as IL-6, IL-1β), and down-regulated the level of central thermoregulatory mediators (PGE2), via multiply involved in TLR4/NF-κB and HSP70/NF-κB signaling pathways. Crucially, 8-OaS treatment significantly reduced the relative abundance of Alistipes (P < 0.01), Odoribacter (P < 0.05) and Alistipes_finegoldii (P < 0.05) in the intestinal flora. The correlation analysis demonstrated that 8-OaS treatment significantly correlated with the increasing on the abundance of Alistipes and levels of 5-hydroxytryptamine (P < 0.01), and tryptamine (P < 0.01). Our findings indicate that 8-OaS exhibits significant antipyretic and anti-inflammatory properties, potentially mediated by intestinal flora and metabolites of neurotransmitters. The results of this study may help to elucidate the antipyretic and anti-inflammatory mechanism of 8-OaS based on intestinal flora and metabolomics analysis.